The multifaceted role of microbiota in liver cancer: pathogenesis, therapy, prognosis, and immunotherapy - Feng, Yun; Han, Meng-Zhen; Zhou, Yu-Hang; Wang, Yi-Wen; Wang, Yue; Sun, Tao; Xu, Jun-Nan (Frontiers in Immunology, 2025)
Accumulating evidence suggests that the progression of hepatocellular carcinoma (HCC) is intricately associated with dynamic alterations in microbiota composition. Disruption of gut microbial homeostasis enables pathogenic gut bacteria to translocate to the liver via the gut-liver axis, where they modulate the tumor microenvironment to promote HCC development. Also, they are associated with anti-tumor immune responses. Studies have confirmed that the microbiota exhibits potential as a biomarker for predicting immunotherapy responses, and its can improve clinical efficacy in the treatment of HCC.This review systematically evaluates current evidence elucidating the regulatory mechanisms by which the microbiota governs the progression of HCC, and explores its synergistic interactions with therapeutic strategies for HCC.